Lex jako „umowa”? : uwagi na podstawie Dig. I 3.1 - Zych, Radosław (Instytut Historyczny Uniwersytetu Wrocławskiego, 2019)
Analysis of the source: Dig. I 3.1, does not allow readers to conclude that the nature of the lex was an “agreement”. Dig. I 3.1 seemed to refer to sponsio, because – according to R. Sohm – it has evolved from the religious act. I believe that the Old Roman sponsio “imposed” by Papinianus in Book one of the Definitiones on the Republican lex was to emphasize its importance in Roman law